KEMISKINAN PADA KELUARGA PENAMBANG PASIR DI TIGA DESA DAERAH ALIRAN SUNGAI TAJUM KABUPATEN BANYUMAS POVERTY OF SAND MINER FAMILY IN THREE VILLAGES AT TAJUM RIVER FLOWING AREA, BANYUMAS REGENCY - , Sudjarwanto; , Sugito (Pembangunan Pedesaan, 2007)
The aim of this research was to know poverty of sand miner family at Tajum river flowing area, Banyumas and their received advocacy. Data were collected from 60 respondents chosen by cluster sampling method. Result of the research showed that respondents worked daily as sand miner in average of 7.25 hours and received their income of Rp10,131.00 or Rp303,979.00 per month. Their low income and high number of family member (average of 4.75 persons) pushed they and their family member to work for additional income. The average of total income was Rp915,382.00 and income per capita was Rp197,712.00. This income was small above poverty line. The economic of sand miner depended on the investors and their participation included their advocacy for improving were needed, because they understood more the miner problems.